Effects of selective laser melting process parameters on 3D-printing of Ti6Al4V/ST316L composite material and their optimization using response surface methodology - Ismaeel, Marwa M.; Al-Dergazly, Anwaar A.; AbdulKareem, Samah K.; Al-Jaburi, Khider (Heritage and Sustainable Development, 2024)
The mechanical properties of Ti6Al4V and ST316L bone implants make them superior to natural bone, which results in fewer contact points with the bone. Different manufacturing processes, such as selective laser melting (SLM), may result in different mechanical properties between Ti-6Al-4V and ST316L implants. Sustainable development for the composite implants was optimized (SLM) in this study to minimize their compressive strength and Young's modulus. A three-dimensional printing process using SLM was optimized based on laser power, hatch distance, laser velocity, and ST316L weight percentage. Composite implants made from titanium alloys and steel alloys were evaluated using response surface methodology (RSM). ST316L composition has been found to influence the mechanical properties of composites in a significant manner, based on the results of parameter optimization. Using Ti6Al4V/ST316L as a biomaterial in knee joint prostheses is possible.